Management of staple line leaks after laparoscopic sleeve gastrectomy: Single-center experience - UPRAK, TEVFİK KIVILCIM; COŞKUN, MÜMİN; UĞURLU, MUSTAFA ÜMİT; GÜNAL, ÖMER; CİNGİ, ASIM; YEGEN, ŞEVKET CUMHUR (My University, 2024)
Objective: In obesity surgery, laparoscopic sleeve gastrectomy (LSG) is a frequently applied method. However, there are certain complications. Leakage is one of the most serious complications after surgery, causing postoperative morbidity and sometimes mortality. There is no consensus about management of leaks after LSG. In our study, we aimed to present our experience on the management of LSG leaks. Patients and Methods: Patients who underwent LSG between 2010-2017 in a tertiary university hospital were analyzed retrospectively. Demographic characteristics, endoscopic and surgical interventions, morbidity, and mortality rates of patients diagnosed with LSG leak were analyzed from prospectively recorded data. Results: Leak was observed in 11 (2.15%) of a total of 510 LSG patients. Six (54%) patients were diagnosed as acute and 5 were early leaks. Stent was applied to most of the patients (72%) with or without surgical exploration. The average length of stay in hospital was 21 days. Mortality was observed in 2 patients. Conclusions: Consequently, leakage after LSG is a complication that requires multimodal therapy. Surgical treatment combined with endoscopic intervention may increase success.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Leakage management; Morbid / surgery; Obesity; Sleeve gastrectomy